The Effect of Pesticides on the Tomato Bacterial Speck Disease Pathogen Pseudomonas Syringae pv. Tomato - Liudmyla Butsenko (Applied Sciences, 2020)
A significant part of the used pesticides does not reach the target organisms and, while remaining in the agrophytocenosis, influences all living organisms in it. Having a toxic and often mutagenic effect, pesticides induce morphological and physiological changes in the cells of microorganisms and are the cause of phenotypic heterogeneity of their populations. However, the effect of pesticides on phytopathogenic bacteria as non-target microorganisms remains out of the field of view for most researchers. However, the use of pesticides can lead to expansion of the diversity of existing phytopathogens and, as a consequence, complications of identification of the pathogens, loss of resistance by plants varieties, and increased harm from diseases caused by them. This study is focused on the effect of pesticides used in tomato plantations on the causative agent of bacterial speck of this crop—Pseudomonas syringae pv. tomato. The studies were carried out using the methods of classical microbiology. The mutagenic action of pesticides was recorded, taking into account the increase of the number of streptomycin resistance mutations in bacteria in the case of pesticide action. It is established that the fungicide aluminium phosethyl is characterised by a bacteriostatic effect on P. syringae pv. tomato. Deltamethrin insecticide does not affect the growth of P. syringae pv. tomato. However, there is an increase in the frequency of streptomycin resistance mutations in both studied strains of P. syringae pv. tomato after using deltamethrin. It is shown that the frequency of occurrence of R (rough colonies) forms of P. syringae pv. tomato IZ28 and IZ46 after using deltamethrin increased by 100 times when in comparison to the frequency of spontaneous morphological dissociation, or smooth-to-rough (S-R) mutation, of these bacteria. Therefore, aluminium phosethyl is characterised by moderate bacteriostatic action against P. syringae pv. tomato. Deltamethrin does not influence the growth of the pathogen of tomato speck but increases the frequency of formation of StrR mutants and R forms of phytopathogenic bacteria.